2018
DOI: 10.1007/s12663-018-1102-7
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Synovial Chondromatosis of the Temporomandibular Joint. Case Series and Systematic Review

Abstract: Aim Synovial chondromatosis (SC) is a benign condition that is characterized by the formation of cartilaginous nodules within the synovial tissue of a joint that may detach and form loose bodies inside the articular space. The purpose of this study is to evaluate the use of surgical arthroscopy for the treatment of SC of the temporomandibular joint (TMJ). Materials and Methods A series of six patients treated with arthroscopy (one patient requiring an open arthrotomy due to the size of the loose bodies) in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Diagnostic wise, TMJ arthroscopy is a real improvement and can also be used for treatment [ 21 ]. Brabyn et al led a systematic review of case reports about patients treated with an arthroscopic approach between 2007 and 2017, concluding that development of CT, MRI imaging, and examination through arthroscopy allowed earlier diagnosis of SC [ 22 ]. Moreover, Fernández Sanromán et al concluded, relying on a case series of five patients, that arthroscopy should become the option of choice as far as treatment is concerned in SC limited to intra-articular localizations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic wise, TMJ arthroscopy is a real improvement and can also be used for treatment [ 21 ]. Brabyn et al led a systematic review of case reports about patients treated with an arthroscopic approach between 2007 and 2017, concluding that development of CT, MRI imaging, and examination through arthroscopy allowed earlier diagnosis of SC [ 22 ]. Moreover, Fernández Sanromán et al concluded, relying on a case series of five patients, that arthroscopy should become the option of choice as far as treatment is concerned in SC limited to intra-articular localizations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the high chondrogenic potential of these “synovial-derived MSC” and the observation that articular cartilage, synovial sub-lining layer and ligaments originate from cells that express growth differentiation factor 5 (GDF5) suggest that cartilage and synovial membrane might have a common embryonic origin [22,23]. In agreement, cases of spontaneous synovial chondromatosis, a benign phenomenon characterized by synovial chondrogenesis, have been reported [24]. Thus, in the joint environment, synovial MSC with a strong chondrogenic potential, which were described several years ago, might correspond to the recently described FLS subset that expresses genes associated with the formation of cartilage, bone and ECM [6].…”
Section: Synovial-derived Mesenchymal Stromal/stem Cells: Where Domentioning
confidence: 84%
“…Secondary synovial chondromatosis has been described, where intraarticular loose bodies instead appear as a result of degenerative arthropathy or trauma [5,6]. PSC affects males up to 3 times more often than women [1] and is most often seen in the knee [7], although any synovial joint may be affected, including the hip [8], shoulder [9], and temporomandibular joint [10]. Patients often present with joint pain and swelling, limited range of motion, crepitus, or may be asymptomatic, depending on the stage, severity, and location of the condition [11,12].…”
Section: Introductionmentioning
confidence: 99%